Etodolac and the risk of acute pancreatitis - Liao Kuan-Fu; Cheng Kao-Chi; Lin Cheng-Li; Lai Shih-Wei (BioMedicine, 2017)
Objective: The aim of this study was to explore the association between etodolac use and acute in Taiwan. Design: We designed a case-control study using the database of Taiwan’s National Health Insurance. Subjects: In all, 7577 subjects aged 20 years or older with newly diagnosed acute pancreatitis were defined as cases, and 27032 sex-matched and age-matched subjects without acute pancreatitis were defined as controls. The period considered for this study was from 1998 to 2011. For the study, never having used etodolac is defined as a subject never receiving a prescription for etodolac. Active use of etodolac is defined as a subject receiving at least 1 prescription for etodolac within 7 days of the date of their being diagnosed with acute pancreatitis. Non-active use of etodolac is defined as a subject not receiving a prescription for etodolac within 7 days but receiving at least 1 prescription for etodolac ≥ 8 days before the date of their being diagnosed with acute pancreatitis. Main outcome measure: The association between etodolac use and acute pancreatitis was estimated by using the multivariable unconditional logistic regression model. Results: After correcting for covariates, the adjusted odds ratio of acute pancreatitis was 3.78 for subjects with active use of etodolac (95% confidence interval 1.11, 12.9), compared with subjects who never used etodolac. The adjusted odds ratio decreased to 1.18 for subjects with non-active use of etodolac (95% confidence interval 0.38, 3.67), but that was without statistical significance. Conclusion: There could be an association between active use of etodolac and acute pancreatitis. Clinicians should take into account the possibility of etodolac-associated acute pancreatitis when patients currently using etodolac present with acute pancreatitis with an unknown cause.